PENGARUH PEMAHAMAN TEKNOLOGI DIGITAL, PROSES BISNIS DAN PENCATATAN KEUANGAN TERHADAP KEBERLANJUTAN BISNIS UMKM DI KECAMATAN KARAWANG BARAT - Dalal Dahlia; Mumun Maemunah; Rohma Septiawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The business sustainability of Micro, Small, and Medium Enterprises (MSMEs) plays a crucial role in ensuring their continuity and readiness to face changes in the digital-based business environment. This study aims to determine how understanding digital technology, business processes, and financial records influence the business sustainability of MSMEs in West Karawang District. The population in this study was all registered MSMEs in West Karawang District. The sampling method used was purposive sampling, resulting in 98 respondents. The data processing technique used was SmartPLS 4 software with the Partial Least Square method, including outer model testing, inner model testing, and hypothesis testing. The results show that understanding digital technology and financial records have a positive and significant impact on MSME business sustainability, while business processes have no significant impact on business sustainability.